Analyzing the nanoindentation response of carbon black filled elastomers. Issue 29 (12th March 2021) - Bouyahia, Zahraa; Mdarhri, Ahmed; Benayad, Anass; Brosseau, Christian; Elaboudi, Ilham; Chicot, Didier; Iost, Alain; He, Delong; Bai, Jinbo
Abstract: Carbon black (CB) filled elastomers are structurally complex materials that offer unique properties at different length scales. They have tremendous potential applications in a number of fields including the automotive and aerospace industries and for designing innovative smart materials such as artificial muscles but their applications remain limited primarily due to inadequate understanding of their unique mechanical properties. Here, using the Berkovich technique to probe the surface mechanical properties at different scales the nanoindentation response of a series of composites made by homogeneously dispersed CB nanoparticles inside a semicrystalline copolymer matrix has been explored. While the measured loading part of the force–displacement curves is well described by Meyer's empirical power relation, the inverted methodology (IM) approach to deal with the unloading part has been considered and its outcome has been compared with that obtained from the standard Oliver–Pharr's method. The results were consistent with the observed increase of hardness when the applied displacement decreases for all composite samples over a large range of CB volume fraction. Zhang and Xu's model is demonstrated to produce experimentally consistent explanation of this indentation size effect. X‐ray photoelectron spectroscopy (XPS) spectra also show composition gradients with depth up to 100 nm. Furthermore, the effect of CB content, surface features, and length scale‐dependent deformation on the hardness–displacement behavior have been considered. These findings highlight the possibility of attaining a diverse set of mechanical properties by a better understanding of the nanoindentation response of CB filled elastomers which can be useful for material selection and design improvements in a number of practical applications. Abstract :